LIQUIDITY RATIO AND PROFITABILITY RATIO ANALYSIS IN ASSESSING FINANCIAL PERFORMANCE - Lestari, Wiwin; Irfan, Irfan (International Proceeding of Law and Economic, 2020)
The research conducted bythe author aims to find out the causes of the decline in liquidity ratios, to find out the causes of the decline in profitability ratios, and to find out and analyze financial performance as measured by liquidity ratios andpro-fitability ratios in PT companies. Garuda Indonesia, Tbk. The research approach uses a descriptive approach, with the object of research seen from the financial statements of PT. Garuda Indonesia in 2013-2018. Where in this study it was carried out byanalyzing financial performance carried out with liquidity ratios and profitability ratios.  The results showed that the cause of the decrease in the liquidity ratio in PT. Garuda Indonesia occurs due to the low number of company assets and the amount of debt that must be paid immediately, even the company's debt exceeds the amount of company assets, the cause of the decrease in the profitability ratio of PT. Garuda Indonesia occurred due to losses incurredin the company due to the company's inability to manage both revenue, total assets and total company equity. The financial performance of PT. Garuda Indonesia during the period 2013 to 2018 was judged from the liquidity ratio said to be liquid or not good, the financial performance of PT. Garuda Indonesia during the period 2013 to 2018 was judged by the profitability ratio in poor manner.